Pengaruh Media Sosial TikTok terhadap Motivasi Belajar Remaja di Surabaya - Dalima, Marisa Novita Angelin; Rahmawati, Aulia (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
The purpose of this research is to ascertain the impact of social media TikTok use on Surabaya teenagers’ motivation to learn. This study is methodology is descriptive quantitative research. The analysis used is causal statistical analysis, which tries to analyze populations or research samples, collect evidence using research instruments, and establish the specified hypotheses. According to the reports’ results, TikTok has a big impact on Surabaya teenagers’ motivation to learn. This demonstrated by the regression equation test results, that Y = 23,346 + 0, 254X, indicating that very increase of one unit in the TikTok score will be followed by an increase of 0,254 with a constant of 23,346 in learning motivation. This study also revealed the impact of the social media TikTok on teenagers in Surabaya through describing its advantages and disadvantages as well as the frequency of uses. Another fact is that teenagers in Surabaya utilize TikTok as a platform for knowledge, information, and enjoyment as well as stress reduction. They do not utilize TikTok as a platform for sharing entertainment content or creating content to achieve more followers. Keywords: TikTok, Motivation to learn, Teenager, Uses and Gratification Theory